2012
DOI: 10.1176/appi.ajp.2011.11020274
|View full text |Cite
|
Sign up to set email alerts
|

An Empirically Derived Taxonomy for Personality Diagnosis: Bridging Science and Practice in Conceptualizing Personality

Abstract: Objective The authors describe a system for diagnosing personality pathology that is empirically derived, clinically relevant, and practical for day-to-day use. Method A random national sample of psychiatrists and clinical psychologists (N=1,201) described a randomly selected current patient with any degree of personality dysfunction (from minimal to severe) using the descriptors in the Shedler-Westen Assessment Procedure–II and completed additional research forms. Results The authors applied factor analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
118
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 44 publications
2
118
0
1
Order By: Relevance
“…It should be noted that some authors share Blatt's original conceptualization of depressive personalities as primarily characterized by anaclitic and introjective variants (Blatt, 1974;Zuroff, 1994;Zuroff & Fitzpatrick, 1995), while others empathize with a more unified perspective, through which an individual with a depressive personality structure is seen as both self-critical and dependent. For example, Westen, Shedler, Bradley, and DeFife (2012) empirically identified a depressive personality syndrome in which both introjective and anaclitic features were salient. Similarly, several authors from different clinical perspectives have suggested a broad variation in the phenotypic expression of narcissism and the existence of two distinct subtypes of narcissistic personalities (Cain, Pincus, & Ansell, 2008;Gabbard & Crisp-Han, 2016;Levy, 2012).…”
Section: Conceptual and Empirical Foundations For A Psychodynamicallymentioning
confidence: 99%
“…It should be noted that some authors share Blatt's original conceptualization of depressive personalities as primarily characterized by anaclitic and introjective variants (Blatt, 1974;Zuroff, 1994;Zuroff & Fitzpatrick, 1995), while others empathize with a more unified perspective, through which an individual with a depressive personality structure is seen as both self-critical and dependent. For example, Westen, Shedler, Bradley, and DeFife (2012) empirically identified a depressive personality syndrome in which both introjective and anaclitic features were salient. Similarly, several authors from different clinical perspectives have suggested a broad variation in the phenotypic expression of narcissism and the existence of two distinct subtypes of narcissistic personalities (Cain, Pincus, & Ansell, 2008;Gabbard & Crisp-Han, 2016;Levy, 2012).…”
Section: Conceptual and Empirical Foundations For A Psychodynamicallymentioning
confidence: 99%
“…By contrast, both traits and dimensional personality disorder diagnoses derived from data provided by experienced clinicians using a systematic clinical research interview correlate in the range of r = .50 to .70 with the same variables as assessed by treating clinicians Westen et al, 2012). Similarly, research on "illusory mental health" (Shedler, Mayman, & Manis, 1993) demonstrates that self-report measures of neuroticism (or negative affectivity) cannot distinguish psychologically healthy individuals from psychologically distressed individuals who lack self-awareness.…”
mentioning
confidence: 94%
“…It can also be accomplished via a prototype matching procedure, whereby diagnosticians gauge the similarity or "fit" between a patient's clinical presentation and a paragraph-length narrative description of each disorder (Rottman, Ahn, Sanislow, & Kim, 2009;Spitzer, First, Shedler, Westen, & Skodol, 2008;Westen & Shedler, 2000;Westen, Shedler, & Bradley, 2006). Elsewhere, we have proposed a dimensional approach to personality diagnosis based on empirically derived personality prototypes (Westen & Shedler, 1999a, 1999bWesten, Shedler, Bradley, & DeFife, 2012). This diagnostic system preserves a syndromal approach to personality, consistent with all editions of DSM to date; however, both the diagnostic groupings and the descriptions of the diagnoses are derived empirically and reflect naturally occurring groupings in the clinical population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical efforts to ascertain hierarchies have failed (7), thus making it difficult for clinicians to determine which personality disorder to diagnose and treat. Although there are a number of explanations for the high rate of PD co-occurrence, it appears that this is an artifact of a criterion count system that does not reflect daily clinical practice, which is closer to a prototype matching system (8,9).…”
mentioning
confidence: 97%